From Readiness to Institutionalized use: Digital Organizational Capability and Public Service Efficiency in Indonesian Local Government - Razak, Muhammad Rais Rahmat; Lubis, Sandi; Adnan, Andi Astinah; Hardianti, Hardianti; Ahmad, Jamaludin (Future Science, 2026)
This study examines how e-government quality and organizational readiness contribute to public service efficiency through the institutionalized use of digital systems in local government. This study reframes e-government usage as an institutionalized administrative practice that connects digital system capability and digital organizational capability with public service performance. A quantitative explanatory design was employed using survey data from 300 civil servants in three cities in South Sulawesi, Indonesia: Makassar, Parepare, and Palopo. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test direct and mediating relationships among e-government quality, organizational readiness, e-government usage, and public service efficiency. The findings show that e-government quality and organizational readiness positively affect public service efficiency. Both variables also significantly influence e-government usage, while e-government usage positively affects service efficiency and mediates the relationships between the two antecedent variables and efficiency outcomes. The model demonstrates strong explanatory power, with R² values of 0.813 for e-government usage and 0.867 for public service efficiency. These results indicate that efficiency gains emerge when reliable digital systems are supported by organizational readiness and are consistently used in administrative processes. The study contributes to digital government literature by positioning e-government usage as an institutionalization mechanism rather than merely a technology adoption variable. Practically, the findings suggest that local governments should align system quality, organizational capability, and standardized digital routines to strengthen sustainable public service efficiency.